Boundary-value problems of nonstationary transfer for generalized energy equation. - E. M. Kartashov; L. M. Ozherelkova; I. V. Antonova (Тонкие химические технологии, 2009)
New analytic solvings of boundary-value problems of transfer for the hyperbolic type equations are surveyed.